Diagnostic Delay Is Associated With Complicated Disease and Growth Impairment in Paediatric Crohn's Disease. (26th September 2020) - Ricciuto, Amanda; Mack, David R; Huynh, Hien Q; Jacobson, Kevan; Otley, Anthony R; deBruyn, Jennifer; El-Matary, Wael; Deslandres, Colette; Sherlock, Mary E; Critch, Jeffrey N; Bax, Kevin; Jantchou, Prevost; et al.
Abstract: Background: Paediatric data on the association between diagnostic delay and inflammatory bowel disease [IBD] complications are lacking. We aimed to determine the effect of diagnostic delay on stricturing/fistulising complications, surgery, and growth impairment in a large paediatric cohort, and to identify predictors of diagnostic delay. Methods: We conducted a national, prospective, multicentre IBD inception cohort study including 1399 children. Diagnostic delay was defined as time from symptom onset to diagnosis >75th percentile. Multivariable proportional hazards [PH] regression was used to examine the association between diagnostic delay and stricturing/fistulising complications and surgery, and multivariable linear regression to examine the association between diagnostic delay and growth. Predictors of diagnostic delay were identified using Cox PH regression. Results: Overall (64% Crohn's disease [CD]; 36% ulcerative colitis/IBD unclassified [UC/IBD-U]; 57% male]), median time to diagnosis was 4.2 (interquartile range [IQR] 2.0–9.2) months. For the overall cohort, diagnostic delay was >9.2 months; in CD, >10.8 months and in UC/IBD-U, >6.6 months. In CD, diagnostic delay was associated with a 2.5-fold higher rate of strictures/internal fistulae (hazard ratio [HR] 2.53, 95% confidence interval [CI] 1.41–4.56). Every additional month of diagnostic delay was associated with a decrease in height-for-age z-score of 0.013 standard deviations [95% CI 0.005–0.021]. Associations persisted after adjusting for disease location and therapy. No independent association was observed between diagnostic delay and surgery in CD or UC/IBD-U. Diagnostic delay was more common in CD, particularly small bowel CD. Abdominal pain, including isolated abdominal pain in CD, was associated with diagnostic delay. Conclusions: Diagnostic delay represents a risk factor for stricturing/internal fistulising complications and growth impairment in paediatric CD. Podcast: This article has an associated podcast which can be accessed at https://academic.oup.com/ecco-jcc/pages/podcast